Utsikt från höghastighetståg : om reseupplevelsens krav på landskapet - Alvarsson Hjort, Agnes (SLU/Dept. of Urban and Rural Development, 2012)
As we travel more and more by train it becomes increasingly important that the time we spend traveling, is of great quality. This has been the foundation of this master thesis and has shaped the outcome of it. The traveling experience, that is, the experience of the landscape that flashes by outside the train window, is an important aspect in railway planning and an aspect that should be taken into greater consideration. The purpose of this master thesis has been to examine how to compose or improve the travel experience for an already planned high speed railway and how the travel experience can be combined with other aspects, which have claims on the landscape. This thesis is based on a literature study and a case study of Ostlänken. The work describes Ostlänken, a planned high speed railway in Sweden between Järna and Linköping, with top speeds at 300-320 kilometers per hour. The railway is part of the larger Götalandsbanan, between Stockholm and Gothenburg, where a journey between these cities should take 2 hours and 15 minutes to compare with today’s minimum of three hours, depending on the number of stops. It also shows how other countries have built their high speed railways and what their goals have been. The work describes the travel experience, what it is, how it can be built up and how it affects the train passengers. The study also examines other claims on the landscape, like agriculture and recreation, and the effects the high speed railway will have on them. The different claims that are examined are agriculture, forestry, infrastructure, cultural landscapes, the image of the landscape, development, recreation and landscape ecology. The effects on the image of the landscape are the most evident, since it is sensitive to changes. The railways stiff framework cuts through and transforms a hilly landscape and can with its large scale construction dominate a small-scale landscape, but if the railway is added with care, it can be a positive addition to the landscape, an identity creator. The railway symbolizes a movement opportunity and a connection to the surrounding world, and also to the human development and technological improvements. A high speed railway leaves traces in the landscape but at the same time it becomes part of the landscape and its history. A good travel experience has many advantages. It´s a way to show the landscapes character that can communicate to the traveler where it is. It can make us relaxed and at ease after a stressful day at work. It can make a long and tedious journey interesting. It has been shown that good environments can have a positive effect on stress recovery. Studies have shown that people recover faster from stress in nature like environments and when listening to sound of the nature, for example birds singing. The travel experience is also an important medium where we can experience the Swedish nature, maybe one of the more prominent mediums since we spend more and more time traveling on train. The travel experience is also a way to show the traveler where they are positioned (where they currently are, in relation to where they are going), which is an important factor for the journey to feel safe. To be able to take the travel experience into consideration in the planning process, there has to be tools to work with. This work has developed methods for analyzing the travel experience for an existing or planned high speed railway, and how to improve it. One method, called movement analysis, was developed during 2010 with Mikael Ohlsson in 2010. The analysis has been further developed and this work shows its area of use. The method analyzes the landscapes spatial forms from an axis, in this case the railway. The spatial formations can then be compared to the speed in which the viewer moves through the landscape and a conclusion of how the spaces will be perceived can be made, if the viewer will be able to experience them at all. The method shows how the landscape varies and how and where you can change it to enhance the travel experience. The method I usable when you need an understanding of how the landscape changes and how it is experienced when people travel through it, but it doesn’t explain if we find the landscape beautiful, exiting or dull. A more detailed example of how the travel experience, for a specific spot, can be enhanced was also added. The analysis for Ostlänken showed that the travel experience had a variation but also included long monotonous stretches where the railway passes through dense forests. To experience an object is not only about if the eye is able to see it, but the following cognitive process is of importance. According to Varming and the Swedish Transport Administration we need about 4 second to be able to perceive an object. If we want to reflect about it before we register something new it takes 20 seconds and we need about one minute to rest our eye on an object or landscape feature. When we travel in higher speeds it becomes more and more difficult to discern object that are close to the train, since we travel to fast to be abler to register it. The object will become a blur, that not only will worsen the travel experience but it can also be an uncomfortable effect. The higher the speed the further away object has to be for us to be able to discern them in a comfortable way. This work has determined how far away from the railway objects has to be for people to be able to perceive and experience them. This is an important factor as it provides a basis for the landscapes spatial requirements, if the landscape is to contribute to the travel experience. The result shows that an object, for example information signs, has to be at least 1400 meters from the train to be able to be discerned if we look out the window in a right angle. If the angle is smaller, about 45 degrees, the object will be in our field of vision longer and we will be able to discern objects closer to us, about 600 meters away. To be able to understand how it feels to travel with high speed train and to see how other countries have built their railways a study trip to Germany was made. The journey went to Frankfurt and Köln and the area between the two cities. This area was chosen because it reminds the most of the landscape Ostlänken passes through. The conclusion from the trip was that in Germany the railway is subordinate to the landscape. They have masked the railway with trees or lowered the ground underneath so that is becomes hidden. Their intention, that the landscape should not be affected visually by the railway, has a negative effect on the travel experience. The travelers will only see trees and bushes that pass in a blur. If the journey can’t offer a good experience it becomes nothing more than transportation from one place to another and the speed and effectiveness of the journey becomes more important The literature and case study showed that a good travel experience offers variation, both in what you can see and how you see it. The railways position in the terrain then becomes important for the outcome of the experience. The question of how to adjust the railway to the landscape is linked to the specific situation and the conflict at hand. There are no given answers to how you solve different conflicts, but it is up to the planner’s creativity to find a solution that not only solves conflict but adds additional qualities to the landscape. The case study examined where the high speed railway should be placed in the landscape so that it would minimize the negative effects, and contribute the most to the travel experience. The place for the case study is situated just north of Norrköping where the open agricultural land meets Bråviken and the fault precipice. The largest problem for the high speed railway is to adjust it to the landscapes varying topography and at the same time keep within the Transportation Administrations chosen corridor. The stiff construction makes it difficult to integrate it with the landscape. The result was that the railway was placed alongside the already existing infrastructure, to minimize the barrier effect that all infrastructure have on the landscape. The railway is also elevated to handle the large changes in topography, but most importantly to enhance the travelers experience by revealing the grand views over the treetops.